2006
DOI: 10.1086/503196
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Variability of Heating in a Solar Active Region

Abstract: Previous studies have indicated that both steady and impulsive heating mechanisms play a role in active region heating. In this paper, we present a study of 20 hours of soft X-ray and EUV observations of solar active region NOAA AR 8731. We examine the evolution of six representative loop structures that brighten and fade first from X-ray images and subsequently from the EUV images. We determine their lifetime and the delay between their appearance in the different filters. We find that the lifetime in the EUV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
57
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 42 publications
12
57
1
Order By: Relevance
“…do not appear to cool down or heat up significantly over timescales of hours Cirtain et al 2007). Our results are in contrast to those obtained by Warren et al (2003); Ugarte-Urra et al (2006Viall & Klimchuk (2011), although they do not necessarily imply steady heating for the single structures. Indeed the higher SDO AIA resolution shows clear variations on timescales of minutes.…”
Section: )contrasting
confidence: 99%
“…do not appear to cool down or heat up significantly over timescales of hours Cirtain et al 2007). Our results are in contrast to those obtained by Warren et al (2003); Ugarte-Urra et al (2006Viall & Klimchuk (2011), although they do not necessarily imply steady heating for the single structures. Indeed the higher SDO AIA resolution shows clear variations on timescales of minutes.…”
Section: )contrasting
confidence: 99%
“…In this scenario, each of the many hundreds to thousands of strands in the loop is heated impulsively and the heating recurrence time on a single strand is longer than a cooling time. Such loops are then expected to be seen sequentially in cooler channels with time, a pattern confirmed in X-ray and EUV observations (Warren et al 2002;Winebarger et al 2003;Winebarger & Warren 2005;Ugarte-Urra et al 2006, 2009. On the other hand, in the so-called hot cores of ARs, some believe the heating to be predominantly steady, meaning that the heating recurrence time on a strand is much less than the cooling time, and that the emission is exclusively hot.…”
Section: Introductionmentioning
confidence: 62%
“…There are also indicators that hydrodynamic evolution along coronal loops can be quite common, especially for active regions. These include observations of coronal rain and catastrophic cooling cycles (Schrijver 2001;Antolin & Rouppe van der Voort 2012;Antolin et al 2015), as well as pervasive cooling signatures observed in extreme ultraviolet (Viall & Klimchuk 2011Auchère et al 2014;Froment et al 2015) and soft X-Ray imaging (Ugarte- Urra et al 2006). A successful heating model should be plausibly consistent with such observations.…”
Section: Introductionmentioning
confidence: 91%